2020
DOI: 10.1002/agj2.20120
|View full text |Cite
|
Sign up to set email alerts
|

Which active optical sensor vegetation index is best for nitrogen assessment in irrigated cotton?

Abstract: Use of active optical sensors (AOS) in nitrogen (N) management of row crops continues to grow. Since the first studies in the mid-1990s, several commercial AOS are now available. Typically, canopy reflectance in red and near infrared (NIR) bands are used to calculate the normalized difference vegetation index (NDVI). More recently, commercially available AOS include a third, red-edge band that allows the calculation of additional vegetation indices (VIs). We present two studies of five site-years of N manageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 34 publications
2
8
0
Order By: Relevance
“…Ultrasonic-sensed cotton canopy heights showed the expected curvilinear growth pattern during the season with the greatest growth rates between first square and mid bloom (Figure 2). Plant heights did not reach a plateau in the second half of the season, as Bronson et al (2020) observed in these same plots with NDVI at mid bloom. Statistical differences between N-fertilized and zero-N plots were observed early in all three seasons at mid-squaring in 2016 and in 2017, and at first square in 2018 (Figure 2).…”
Section: Resultssupporting
confidence: 74%
“…Ultrasonic-sensed cotton canopy heights showed the expected curvilinear growth pattern during the season with the greatest growth rates between first square and mid bloom (Figure 2). Plant heights did not reach a plateau in the second half of the season, as Bronson et al (2020) observed in these same plots with NDVI at mid bloom. Statistical differences between N-fertilized and zero-N plots were observed early in all three seasons at mid-squaring in 2016 and in 2017, and at first square in 2018 (Figure 2).…”
Section: Resultssupporting
confidence: 74%
“…Petiole NO 3 concentration sampling can then be used to complement the soil test approach as an in-season assessment of N status for in-season N adjustments and to guide the timing of N applications. In addition to petiole sampling, in-season N status can be done with proximal sensing using active optical sensors (Bronson et al, 2019(Bronson et al, , 2020. We can compare the dates when N deficiency in petiole NO 3 in zero-N or reduced-N reflectance-based N management plots were detected in the Maricopa studies with the dates when published vegetation indices, calculated from active optical sensor-measured canopy reflectance detected N deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…We can compare the dates when N deficiency in petiole NO 3 in zero-N or reduced-N reflectance-based N management plots were detected in the Maricopa studies with the dates when published vegetation indices, calculated from active optical sensor-measured canopy reflectance detected N deficiency. In many cases, petiole NO 3 indicated N deficiency 1-4 wk before the active optical sensors did (Bronson et al, 2019(Bronson et al, , 2020. For instance, with OSI in 2014, petiole NO 3 levels in zero-N plots were less than soil test plots 54 DAP, whereas NDRE showed this difference 82 DAP (Day of Year 203) (Bronson et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Red-edge based vegetation indices are also less prone to saturation and have provided stronger relationships with lint yield compared with red or green-based vegetation indices in previous studies (Ballester et al, 2017;Bronson et al, 2020;Raper & Varco, 2015). However, Landsat 7-8 (used F I G U R E 6 Observed cotton lint yields and predicted yield maps for Fields 1 and 2 at Mungindi (New South Wales) using the gradient boosting machine (GBM) model at the flowering stage and the random forests (RF) model at the boll-fill stage using all variables in the current study) was not equipped with red-edge and was the only publicly available multispectral satellite imagery available during all seasons and at a within-field resolution.…”
Section: Model Performancementioning
confidence: 94%